“Spazi di gioco”. Musei, modalità di narrazione in rete e audience development - Liguori, Daniela (Aesthetica Preprint, 2023)
The paper aims to highlight how the guidelines promoted by the European Union to direct cultural organisations towards policies and practices always more characterised by audience-centricity – this through a thoughtful use of new technologies – involve issues that are at the heart of the aesthetic debate starting from the famous essay The work of art in the Age of Mechanical Reproduction by Walter Benjamin: changed production’s conditions and use of works of art; enjoyment of the traditional categories of the philosophy of art (the genius, the contemplation and so on); the political function of art. The paper also aims to show how these issues are fundamental for a rethinking of the modes of telling by which museums can promote the material and immaterial heritage of their collections by accepting the challenge of a time that, like today, is characterised by the explosion of digital technologies and by the pervasive deployment of network connectivity and of practices of networking.